2011
DOI: 10.1111/j.1365-2125.2011.03966.x
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol – pills to replace a healthy diet?

Abstract: Nutrapharmacology, or the use of bioactive food compounds at pharmacological doses is emerging as a therapeutic approach to target the complex metabolic dysregulations in ageing and obesity-related chronic disease. Resveratrol, a polyphenol found in the skin of grapes, and other edible plants and related food products, has received extensive attention through the link with the French paradox, and later with its chemopreventive activity demonstrated in vitro and in animal cancer models. A plethora of laboratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(85 citation statements)
references
References 103 publications
(160 reference statements)
0
84
0
1
Order By: Relevance
“…Resveratrol (3, 5, 4'-trihydroxy-trans-stilbene) is a naturally occurring polyphenol, which activates AMPK and SIRT1; thereby, it mimics a condition of caloric restriction as shown in a number of in vitro and in vivo studies [20,21]. The presented meta-analysis shows that there is no sufficient evidence to support the efficacy of resveratrol in the management of NAFLD, as resveratrol did not show a significant reduction in the degree of fibrosis, or in the level of markers of liver damage and inflammatory markers.…”
Section: Summary Of the Main Resultsmentioning
confidence: 99%
“…Resveratrol (3, 5, 4'-trihydroxy-trans-stilbene) is a naturally occurring polyphenol, which activates AMPK and SIRT1; thereby, it mimics a condition of caloric restriction as shown in a number of in vitro and in vivo studies [20,21]. The presented meta-analysis shows that there is no sufficient evidence to support the efficacy of resveratrol in the management of NAFLD, as resveratrol did not show a significant reduction in the degree of fibrosis, or in the level of markers of liver damage and inflammatory markers.…”
Section: Summary Of the Main Resultsmentioning
confidence: 99%
“…22,23 Evidence shows that resveratrol possesses various anti-inflammatory activities, such as decreasing neuroinflammation, chronic inflammation, and cytokine-mediated inflammations. 24,25 In addition, hopeaphenol and (+)-eviniferin, resveratrol derivatives in VT, were also reported to have anti-inflammatory effects. 2,26 Studies have demonstrated that two components are neuroprotective and improve vascular function.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, an inhibitory effect of 11b-HSD1 activity in microsomes of rat adipose tissue was observed at 1 mM resveratrol. According to the amount of resveratrol in the foods (Chachay et al 2011), the appearance of 1 mM resveratrol in blood is equivalent to the ingestion of 13.7-27.4 g fresh grape skin or 130 ml red wine (pinot noir). Therefore, it seems possible to ingest this amount of resveratrol daily.…”
Section: Figurementioning
confidence: 99%
“…Similar to most polyphenols, resveratrol has antioxidant activity. It is commonly found in fresh grape skins, red wine (pinot noir), boiled peanuts, and blueberries (dry sample) at 5-10 mg/100 g, 10.5 mg/l, 0.52 mg/100 g, and 0.4 mg/100 g respectively (Chachay et al 2011). As an ingredient of red wine, resveratrol explains the epidemiological phenomenon called the 'French paradox', in which red wine consumption is associated with a low incidence of cardiovascular disease (Petrovski et al 2011, Smoliga et al 2011, Turan et al 2012.…”
Section: Introductionmentioning
confidence: 99%